STRATEGI PEMASARAN DALAM MENINGKATKAN JUMLAH PENJUALAN PADA HOME INDUSTRY SUIIP DESA KARANGREJO KABUPATEN TULUNGAGUNG - Yossy Inka Febriani; Siswahyudianto Siswahyudianto (Universitas Nusa Cendana, 2022)
7P marketing mix strategy is one of marketing strategies that has been widely used in every field of business. The purpose of this research is to analyze the marketing strategies that have been implemented in home industry SUIIP that is a ‘kembang goyang’ producer. This study is using qualitative research where data collection obtained from interview techniques and direct observation into the business. Results of this study indicate that implementation of 7P’ marketing mix strategy contributes to fluctuative number of sales. It is necessary to evaluate every aspect of marketing strategy that has been implemented so that it continues to development of innovating products and increasing of the business competitiveness. Keywords: Marketing Strategy, 7P Marketing Mix, Total Sales